Advances in mechanical and electronic engineering : Volume 1 - Lin, Sally; Jin, David (Lecture Notes in Electrical Engineering, 2012)
This book includes the volume 1 of the proceedings of the 2012 International Conference on Mechanical and Electronic Engineering(ICMEE2012), held at June 23-24,2012 in Hefei, China. The conference provided a rare opportunity to bring together worldwide researchers who are working in the fields. This volume 1 is focusing on Mechanical Engineering and Automation as well as Vehicle Engineering and Technology.